Molecular insight into the docking of lysophosphatidylethanolamine (lysoPE)-22:6 interaction with GPR119: Acute exposure to an electric field induces changes in human plasma lysoPE-22:6 and lysoPE-20:4 levels. Issue 5 (2017) - Nakagawa-Yagi, Yuzo; Hara, Hiroyuki; Nakanishi, Hiroki; Kanai, Chisato; Hara, Akikuni
No abstract available